″ Formation of special competences of future geography teachers in the process of educational practice: the regional aspect″ - Borysenko, K. B. (Problems of Engineer-Pedagogical Education, 2018)
The article analyzes the problems of the development of special competences of future geography teachers during educational practices at the regional level. It is recommended to organize the educational process in such a way as to ensure the formation and development of special competences in accordance with the competence model of the specialist. The technology of special competences formation is outlined; the role of educational practices in this process is specified. The work provides a detailed analysis of scientific sources on the subject matter and highlights procedural aspects of the special competences formation. The present work is a logical continuation of the author's previous works on teaching and methodological substantiation of the process of the development of special competences of the future geography teacher in the process of educational practices. The emphasis is placed on the regional peculiarities of educational practices conducted in the classical university, with particular attention being paid to the need for seasonal observations, nature expeditions and excursions throughout the academic year. The work also details the components of special competences acquired by students in the process of going through certain stages of practice.